SINTESIS DAN KARAKTERISASI ZEOLIT FAUJASIT DARI LIMBAH BATUBARA OMBILIN DENGAN METODA ALKALI HIDROTERMAL AIR LAUT - Upita Septiani; Widya Yuliani Fatiha; Syukri Arief (Universitas Andalas, 2015)
Zeolite synthesis using Ombilin coal fly ash at low temperature with alkaline hydrothermal process has been carried out. The used Fly ash was melted by NaOH at a temperature of 550°C. Alkaline hydrothermal processes in zeolite synthesis performed with variations of temperature at 35°C , 45°C and 60°C . The zeolite that obtained was characterized by using Fourier Transform Infra Red (FT - IR), X - Ray Diffraction (XRD) , Scanning Electron Microscopy (SEM) in combination with EDX . The characterization results showed the formation of zeolite were better when an increasing in temperature processes and the use of sea water as a solvent. On the use of seawater, were obtained sodalit zeolite with the chemical formula Na8(Al6Si6O24)Cl2.